2020
DOI: 10.1063/5.0028363
|View full text |Cite
|
Sign up to set email alerts
|

Carrier recombination and diffusion in high-purity diamond after electron irradiation and annealing

Abstract: Carrier transport mechanisms are studied in high purity CVD diamond irradiated with 6 MeV electrons in the 10 12 -10 16 cm -2 dose range and annealed at different temperatures up to 1450 C o . Lifetimes and diffusion coefficients are extracted using two different pump-probe techniques based on the free-carrier-absorption and the transient grating principles and correlated with the corresponding defect evolution from spectroscopic measurements. The neutral monovacancy is revealed to be the main carrier recombin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…[ 53 ] An experimental study of the electronic properties of electron‐irradiated high‐purity CVD diamonds showed in addition that irradiation leads to a strong drop in the lifetime of free charge carriers, due to their fast recombination with vacancy‐associated defects. [ 22 ] Photoluminescence and optical absorption measurements performed on these irradiated samples after annealing at various temperatures enabled to demonstrate that the dominant recombination center was the single vacancy for samples annealed below 900 °C and the divacancy for samples annealed between 900 °C and 1000 °C. [ 22 ] It was in addition established that the neutral single vacancy presented a high capture cross‐section (6.3 × 10 –16 cm 2 , versus 1 × 10 –16 cm 2 for N s 0 ).…”
Section: Discussion On the Nature Of Low‐ionization Energy Defects In...mentioning
confidence: 99%
See 2 more Smart Citations
“…[ 53 ] An experimental study of the electronic properties of electron‐irradiated high‐purity CVD diamonds showed in addition that irradiation leads to a strong drop in the lifetime of free charge carriers, due to their fast recombination with vacancy‐associated defects. [ 22 ] Photoluminescence and optical absorption measurements performed on these irradiated samples after annealing at various temperatures enabled to demonstrate that the dominant recombination center was the single vacancy for samples annealed below 900 °C and the divacancy for samples annealed between 900 °C and 1000 °C. [ 22 ] It was in addition established that the neutral single vacancy presented a high capture cross‐section (6.3 × 10 –16 cm 2 , versus 1 × 10 –16 cm 2 for N s 0 ).…”
Section: Discussion On the Nature Of Low‐ionization Energy Defects In...mentioning
confidence: 99%
“…[ 22 ] Photoluminescence and optical absorption measurements performed on these irradiated samples after annealing at various temperatures enabled to demonstrate that the dominant recombination center was the single vacancy for samples annealed below 900 °C and the divacancy for samples annealed between 900 °C and 1000 °C. [ 22 ] It was in addition established that the neutral single vacancy presented a high capture cross‐section (6.3 × 10 –16 cm 2 , versus 1 × 10 –16 cm 2 for N s 0 ). Considering that sample 6 used in our study was annealed at 700 °C, the recombination of charge carriers with the single vacancy is the most likely.…”
Section: Discussion On the Nature Of Low‐ionization Energy Defects In...mentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, in the case of in-plane experiments, the intercontact distance (a hundreds of micrometers) is significantly larger in comparison with the linear size of plates (about micrometer) resulting in pronounced influence of interface recombination and scattering on the observed photoelectrical properties. According to the light induced transient grating method [28][29][30], the diffusion coefficient of charge carriers in the BOS films does not exceed 0.01 cm 2 /s, whereas their lifetime equals to a few tens of picoseconds [23]. Interface recombination results in reduction of non-equilibrium concentration of charge carriers under steady-state illumination, and their scattering at the inter-particle interfaces leads to the decrease of their mobility.…”
Section: Electrical Properties Of the As-prepared Filmsmentioning
confidence: 99%
“…Fundamental transport studies are focusing on the high mobility of carriers in diamond. Konishi et al 44 reported the highest recorded mobility-lifetime product of 0.2 cm 2 /V at low temperature in highpurity synthetic diamond, and Grivickas et al 45 49 implemented the high-temperature conductance method to study the Al 2 O 3 /B-doped diamond interface states. Moreover, Mirabedini et al 50 reported a first-principles study of the structural and electronic properties of 2D layer (graphene and h-BN)/hydrogen-terminated diamond (100) heterostructures.…”
mentioning
confidence: 99%